Effect of Sand Percentage on the Compaction Properties and Undrained Shear Strength of Low Plasticity Clay - Alkroosh, Iyad; Al-Robay, Ali; Sarker, Prabir; Alzabeebee, Saif (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
This paper investigates the influence of sand content on the mechanical behavior of a low plasticity clay that collected from south of Iraq (Sumer town). Samples have been prepared with sand contents of 0%, 10%, 20%, 30%, and 40% of the clay weight. Standard Proctor and unconfined compression tests have been carried out and the optimum moisture content, maximum dry density, and undrained shear strength have been determined. The results show a gradual increasing trend of the maximum dry density with the increase of the sand content up to 30%. The highest dry density reaches 1.90 g/cm3 corresponding to an optimum moisture content of 12%. In addition, this paper shows that the undrained shear strength is inversely proportional to the increase of the percentage of sand. The results of this work provide a useful addition to the literature regarding the behaviour or low plasticity clay-sand mixture.